1986
DOI: 10.1111/j.1469-7998.1986.tb03609.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of various mammalian tendons

Abstract: Dynamic tensile tests have been performed, using physiologically relevant frequencies and stress ranges, on various tendons from the legs and tails of 10 species of mammal. No consistent differences were found between tendons from different species or different anatomical sites. Tangent Young's modulus increases from low values at low stresses to about 1·5 GPa at stresses exceeding 30 MPa. Percentage energy dissipations of 6 to 11% have been measured for different species, but the lower values are probably the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
222
6
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(256 citation statements)
references
References 19 publications
(17 reference statements)
23
222
6
2
Order By: Relevance
“…The problem with studying excised tendons is the difficulty attaching a cut tendon to a puller and knowing what part of the tendon is held firm and what part is allowed to stretch. In a careful study by Bennett et al (2), attempts were made to determine whether the stress-strain relationship is constant for tendons of different mammalian species. They concluded that the difference between species was small compared with the error of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The problem with studying excised tendons is the difficulty attaching a cut tendon to a puller and knowing what part of the tendon is held firm and what part is allowed to stretch. In a careful study by Bennett et al (2), attempts were made to determine whether the stress-strain relationship is constant for tendons of different mammalian species. They concluded that the difference between species was small compared with the error of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the presence of elastic tissue may in fact be a phylogenetic constraint of the vertebrate musculoskeletal system wherein long tendons are needed to allow the proximal location of muscle mass and that performance may actually suffer because of this. The collagen fibres in tendon have a Young's modulus of 1.5×10 9 N m −2 (Bennett et al 1986), which although high for flexible biological tissues, is much lower than the 200×10 9 N m −2 found in steel cable (Vogel 1998). Elastic storage may be unavoidable instead of desirable, which is an important consideration when building robots.…”
Section: Introductionmentioning
confidence: 99%
“…This unusual property is thought to derive from the varying angle of collagen fibrils throughout the fascicle, which was observed to vary depending on the biological role of the tendon, and affects its elastic response [65]. This is notably efficient: under stresses of 20 MPa and frequencies of 1-2 Hz, tendon tissues were shown to return up to 93 % of strain energy [66].…”
Section: Tendons-release Of Stored Energymentioning
confidence: 99%